Women and media. Institutional cultures, inequality and dynamics of power: 1982 to 2002 - Quiroga, Sergio Ricardo (Cuestiones de Género: de la igualdad y la diferencia, 2016)
This paper studies the participation of women in the media seeking to examine whether there was discrimination against them, the characteristics of female employment, institutional cultures and the dynamics of power in the period between 1982 and 2002 in the city of Villa Mercedes, San Luis, Argentina. This development is also a research effort to try to display the status of women in the media world in a certain context and historical moment. Stereotypical representation of female workers in the media has been one of the central themes of the first reviews and studies on communication and gender. Using tools of qualitative methodology using document analysis and semi-structured interviews examine the institutional and dynamic cultures of power in women who worked in the media in the city of Villa Mercedes, San Luis.